National heritages and the new Europe - Larkham, Peter J. (European Spatial Research and Policy, 1994)
This paper argues that the use of national heritage, principally as formed in the built environment, is significant in the formulation of a Europe-wide sense of belonging. National heritages have been widely manipulated in the past to serve nationalist purposes, and the long history of Europe has led to a heritage characterized by conflict implying a form of “supra-nationalism”: war, oppression, presecution, even genocide. Yet for purposes of integration, planners and economic development authorities are now marketing heritage. Which heritage and whose are important questions. Any heritage planning is an overtly political action; but it is suggested that, rather than manufacturing a new, trans-European heritage which would be patiently artificial and superficial, a trans-national regional heritage should be built up. Europe has many heritages; they are often very local; and they should be used to the best advantage in the changing socio-political climate of the next two decades.